Biomimetic Approach to Evaluate Mineralization of BAG-Containing Resin Composite. (2022) - Yun, J.; Tsui, K.-H.; Fan, Z.; Burrow, M.F.; Matinlinna, J.P.; Wang, Y.; Fok, A.; Tsoi, J.K.H.
Abstract : Purpose/Aim: This study aims at explores immersion solutions other than standard SBF that could evaluate mineralization of dental resin composites containing low percentage bioactive glass (BAG). Materials and Methods: Experimental UDMA/TEGDMA resin composites containing total 25 vol% glass fillers (with 0.0, 1.9, 3.8 or 7.7 vol% of 45S5 bioactive glass (BAG) fillers) were prepared. The specimens were immersed in three different solutions either with bicarbonate which are Hanks balanced salt solution (HBSS) and cell culture medium (MEM), or without bicarbonate which is a novel Simple HEPES-containing Artificial Remineralization Promotion (SHARP) solution, for 3, 7 and 14 days. These solutions were then analyzed by ICP-OES and pH, and the surfaces of the BAG composites were analyzed by SEM, XRD and FTIR. Results: ICP-OES revealed Ca and P concentration continuously decrease, while Si concentration increases with time in all groups. Only SHARP solution is able to maintain a constant pH over the immersion time. SEM, together with XRD and FTIR, showed nano-sized octacalcium phosphate (OCP) nanospheres formation on 3.8 and 7.7 vol% BAG composites after 14 days immersion in HBSS (500-600 nm) and MEM (300-400 nm). SHARP solution enabled OCP formation after 3 days and then self-assembled into urchin-like carbonated hydroxyapatite (CHA) microspheres encompassed with nanorods of 100 nm width and 8 m length after 14 days of immersion for 7.7 vol% BAG composites. Conclusions: This study suggests the SHARP solution can evaluate mineralization biomimetically whereas CHA microspheres can be formed on BAG-containing resin composites.